(3eNJUQ LGeY GdCUhd deLO GdOjf GHf GdCKjQs - (3eMeO GdeRhRis; (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO GHf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s ((3eMeO Hf ESMGb Hf YeQ GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO aEfi ChOYJ gPG GdcJGH CMGOjK Yf QShd Gddg Udi Gddg Ydjg hSde eeG GfJNHJg ef GdcJGH GdeSei LGeY GdCUhd s
(3BNQgG (B:s
(3bGd QLd dQShd Gddg Udi Gddg Ydjg hSde (B: (3CYbdgG hCJhcd Ch CWdbgG hCJhcd bGd (B: (3GYbdgG hJhcd BNQLg GdJQePi Je GdcJGH s
(3GdfSNI HgG MhGTs
(3HBNQgG SJ hQbGJ ai PcQ LeGYI ef GdCfHjGA GdePchQjfs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B272 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B174s
Keywords: (3CUhd Gdabgs